Current smoking status may be associated with overt albuminuria in female patients with type 1 diabetes mellitus: a cross-sectional study - Okada, Kenta (BioMed Central, 2012)
BACKGROUND: There are very few clinical reports that have compared the association between cigarette smoking and microangiopathy in Asian patients with type 1 diabetes mellitus (T1DM). The objective of this study was to assess the relationships between urinary protein concentrations and smoking and gender-based risk factors among patients with T1DM. METHODS: A cross-sectional study of 259 patients with T1DM (men/women = 90/169; mean age, 50.7 years) who visited our hospital for more than 1 year between October 2010 and April 2011 was conducted. Participants completed a questionnaire about their smoking habits. Patient characteristics included gender, age, body mass index, blood pressure, hemoglobin A1c, lipid parameters, and microangiopathy. Diabetic nephropathy (DN) was categorized as normoalbuminuria (NA), microalbuminuria (MA), or overt albuminuria (OA) on the basis of the following urinary albumin/creatinine ratio (ACR) levels: NA, ACR levels less than 30 mg/g creatinine (Cr); MA, ACR levels between 30 and 299 mg/g Cr; and OA, ACR levels over 300 mg/g Cr. RESULTS: The percentages of current nonsmokers and current smokers with T1DM were 73.0% (n = 189) and 27.0% (n = 70), respectively. In addition, the percentage of males was higher than that of females (52.2% versus 13.6%) in the current smoking population. The percentage of DN was 61.8% (n = 160) in patients with NA, 21.6% (n = 56) in patients with MA, and 16.6% (n = 43) in patients with OA. The percentage of males among OA patients was also higher than that of females (24.4% versus 12.4%). However, current smoking status was associated with OA in females with T1DM only [unadjusted odds ratio (OR), 4.13; 95% confidence interval (CI), 1.45–11.73, P < 0.01; multivariate-adjusted OR, 5.41; 95% CI, 1.69–17.30, P < 0.01]. CONCLUSIONS: Based on our results in this cross-sectional study of Asian patients with T1DM, smoking might be a risk factor for OA among female patients. Further research is needed of these gender-specific results.